Development and validation of a 3ABC antibody ELISA in Australia for foot and mouth disease. Issue 6 (June 2014) - Colling, A; Morrissy, C; Barr, J; Meehan, G; Wright, L; Goff, W; Gleeson, LJ; van der Heide, B; Riddell, S; Yu, M; Eagles, D; Lunt, R; et al.
<x xml:space="preserve">Abstract</x> Objective To measure the diagnostic performance of an Australian‐developed ELISA for the detection of antibodies against the non‐structural proteins (NSP) 3ABC of the foot and mouth disease (FMD) virus. Design Test development and validation study. Methods The diagnostic specificity was determined using 2535 sera from naïve animals and 1112 sera from vaccinated animals. Diagnostic sensitivity was calculated from the data for 995 sera from experimentally and field‐infected animals from FMD‐endemic countries in South East Asia. A commercial ELISA detecting antibodies against FMD virus NSP was used as the reference test to establish relative sensitivity and specificity. Bayesian latent class analysis was performed to corroborate results. The diagnostic window and rate of detection were determined at different times using sera from cattle, sheep and pigs before and after infection, and after vaccination and subsequent infection. Repeatability and reproducibility data were established. Results At 35% test cut‐off, the 3ABC ELISA had an overall diagnostic sensitivity of 91.5% and diagnostic specificity of 96.4%. The diagnostic sensitivity in vaccinated and subsequently infected cattle was 68.4% and diagnostic specificity in vaccinated cattle was 98.0%. Conclusions The 3ABC ELISA identified field and experimentally infected animals, as well as vaccinated and subsequently infected animals. Diagnostic sensitivity and specificity estimates for other FMD NSP tests are comparable with the results obtained in this study. This NSP ELISA was found to be 'fit for purpose' as a screening assay at the herd level to detect viral infection and also to substantiate absence of infection.